Finite Element Method (FEM) Model and Performance Analysis of Solid Oxide Fuel Cells - Geisler, Helge Ingolf (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik, 2019)
This work presents a numerical FEM framework, capable of predicting SOFC performance under technically relevant, planar stack contacting conditions. A high level of confidence in the model predictions is supplied by using exclusively experimentally determined material/kinetic parameters and by a comprehensive validation. The presented model aids SOFC stack development by pre-evaluating possible material choices and design combinations for cells/interconnectors without any experimental effort.